2006
DOI: 10.1021/ja0634369
|View full text |Cite
|
Sign up to set email alerts
|

Template Ordered Open-Grid Arrays of Paired Endohedral Fullerenes

Abstract: Developing useful molecular systems, such as planar networks of molecules for novel molecular-electronic architectures, 1-4 requires the ability to control the way molecules assemble at surfaces. Many techniques exploit non-covalent directional bonding interactions between molecules, such as hydrogen bonding, to facilitate the molecular assembly process. [5][6][7][8][9] However, if the molecules lack such directional bonding attributes then it becomes difficult to develop novel molecular architectures using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 24 publications
1
34
0
Order By: Relevance
“…The formation of planar hexagonal close-packed islands at elevated temperatures ($250°C) has also been observed for Er 3 N@C 80 on the non-stoichiometric SrTiO 3 (0 0 1)-c(4 · 2) surface [8]. However, on this surface the islands self-assemble on the terraces rather than on the step edges and do not exhibit an epitaxial relationship with the substrate.…”
Section: Substrate-fullerene Interactionsmentioning
confidence: 63%
See 1 more Smart Citation
“…The formation of planar hexagonal close-packed islands at elevated temperatures ($250°C) has also been observed for Er 3 N@C 80 on the non-stoichiometric SrTiO 3 (0 0 1)-c(4 · 2) surface [8]. However, on this surface the islands self-assemble on the terraces rather than on the step edges and do not exhibit an epitaxial relationship with the substrate.…”
Section: Substrate-fullerene Interactionsmentioning
confidence: 63%
“…Encapsulation of fullerenes in a carbon nanotube provides a means for producing one-dimensional arrays, whilst direct deposition onto a surface can create twodimensional networks. Custom-made two-dimensional networks with controlled spacings between fullerenes may be created using supramolecular [5][6][7] or structural [8,9] templates. Regular arrays of qubits open the door for global addressing schemes for quantum information processing, and two-dimensional networks have the advantage of being able to employ much more powerful error correction techniques [10].…”
Section: Introductionmentioning
confidence: 99%
“…One way to privilege the growth of one of the networks would be to change the supporting surface to tune the molecule−surface interaction. 70,71 ■ CONCLUSION…”
Section: ■ Discussionmentioning
confidence: 99%
“…Therefore, direct growth of graphene on the surface of high‐k dielectric and scatter‐screening dielectric substrates becomes significant. SrTiO 3 (STO), a transparent, high‐k perovskite dielectric may have great thermal stabilities and potentials 60, 61, 62. Sun et al demonstrated the metal‐catalyst free direct CVD growth of graphene on STO (001) substrates using a simple APCVD technique (Ar/H 2 /CH 4 :100/50/2.5 sccm) 63.…”
Section: Catalyst‐free Direct Cvd Growth Of Graphene On Technologicalmentioning
confidence: 99%